2021
DOI: 10.1073/pnas.2110472118
|View full text |Cite
|
Sign up to set email alerts
|

Rapid cloud removal of dimethyl sulfide oxidation products limits SO 2 and cloud condensation nuclei production in the marine atmosphere

Abstract: Oceans emit large quantities of dimethyl sulfide (DMS) to the marine atmosphere. The oxidation of DMS leads to the formation and growth of cloud condensation nuclei (CCN) with consequent effects on Earth’s radiation balance and climate. The quantitative assessment of the impact of DMS emissions on CCN concentrations necessitates a detailed description of the oxidation of DMS in the presence of existing aerosol particles and clouds. In the unpolluted marine atmosphere, DMS is efficiently oxidized to hydroperoxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 51 publications
3
45
1
Order By: Relevance
“…As discussed in G. A. Novak et al. (2021), we find that multiphase chemistry has an irreversible and significant impact on [HPMTF] suppressing OCS production. The addition of HPMTF multiphase chemistry reduces P OCS from 680.1 to 52.9 Gg S yr −1 with the largest differences found in regions of high cloud cover at high latitudes (Eastman et al., 2011; King et al., 2013; Figure 3a).…”
Section: Global Estimates Of Ocs Production From Dms Oxidationsupporting
confidence: 71%
See 2 more Smart Citations
“…As discussed in G. A. Novak et al. (2021), we find that multiphase chemistry has an irreversible and significant impact on [HPMTF] suppressing OCS production. The addition of HPMTF multiphase chemistry reduces P OCS from 680.1 to 52.9 Gg S yr −1 with the largest differences found in regions of high cloud cover at high latitudes (Eastman et al., 2011; King et al., 2013; Figure 3a).…”
Section: Global Estimates Of Ocs Production From Dms Oxidationsupporting
confidence: 71%
“…This approach is compared with the existing, fixed-yield model where 𝐴𝐴 𝐴𝐴OCS = 𝑌𝑌OCS × 𝐿𝐿DMS , 𝐴𝐴 𝐴𝐴OCS = 0.7% and 𝐴𝐴 𝐴𝐴DMS is the loss rate of DMS to reaction with OH or 𝐴𝐴 𝐴𝐴DMS+OH[OH][DMS] . We used the GEOS-Chem global chemical transport model with an expanded DMS oxidation mechanism and model updates to halogen chemistry and cloud processing (Holmes et al, 2019;G. A. Novak et al, 2021;Veres al., 2020;Wang et al, 2019Wang et al, , 2021version 12.9.2, www.geos-chem.org, see in Supporting Information S1 for more details).…”
Section: Global Estimates Of Ocs Production From Dms Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning aerosol production, organic photochemistry is not considered at all in climate models as it is computationally expensive. Efforts are being made to include the chemistry of DMS from marine biogenic emissions as it has been recognised as important for the Earth's climate being an efficient aerosol and cloud droplet producer (Fung et al., 2022; Grandey & Wang, 2015; Mayer et al., 2020; Novak et al., 2021). We showed that butenes may also contribute to marine NPF, deserving a place in climate models that currently account for “unknown organic emissions” with a scaling factor applied to DMS emissions (Bodas‐Salcedo et al., 2019; Mulcahy et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The original paper applied entrainment-limited uptake to first-order loss of nitrogen oxide compounds (NO 2 , NO 3 , N 2 O 5 ) and showed that clouds are a globally significant sink for these gases (Holmes et al, 2019). The method has since been applied to nitrogen oxide isotopes (Alexander et al, 2020), nitrate in urban haze (Chan et al, 2021), dimethyl sulfide oxidation products (Novak et al, 2021;Jernigan et al, 2022), mercury (Shah et al, 2021), and reactive halogens (Wang et al, 2021), all of which also involved first-order loss reactions in clouds. This note derives entrainment-limited reaction kinetics for bimolecular reactions with second-order kinetics so that the entrainment-limited method can be applied to a wider range of chemical systems that are important in the atmosphere.…”
Section: Introductionmentioning
confidence: 99%